Shareholder value diminution through long-term debts: Evidence from the Nigerian oil industry - Ikwuo, Ama Kalu; Nwite, Isaiah Michael; Nworie, Gilbert Ogechukwu; Nworie, Fidelia Nkechi (goodwood publishing, 2025)
Purpose: Failure to maintain an optimal balance between the benefits of long-term debts and the risks associated with financial distress often results in the erosion of shareholder value. In view of the above problem, this study examined whether long-term debts affect shareholder value diminution among listed oil and gas firms in Nigeria. Research Methodology: The ex-post facto research design was deployed on a sample of five firms purposively selected from a population of nine listed oil and gas firms in Nigeria. Secondary data were sourced from the firms’ annual reports between 2014-2023. The hypotheses were tested using panel-estimated generalised least squares. Results: An increase in long-term debt to asset ratio significantly contributes to shareholder value diminution (? = -42.56871; p-value of 0.0003); an increase in long-term debt to equity ratio significantly contributes to shareholder value diminution (? = -5.441092; p-value of 0.0005). Limitations: The study sampled only five out of nine listed Nigerian oil and gas firms and relies solely on net assets per share to measure shareholder value, which may not fully capture the industry's broader financial dynamics. Contribution: In conclusion, the over-reliance on long-term debt financing contributes to heightened financial vulnerability as well as sabotages the aim of maximising shareholders wealth. We recommend that the management of companies in the Nigerian oil and gas industry implement stricter controls on their long-term debt-to-asset ratios by setting a threshold beyond which debt levels should not increase in order to avoid significant shareholder value erosion.